Relationship between social skill and learning outcomes of biology student on basic chemistry course - Syarifa Wahidah Al Idrus; Jono Irawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims at determining the level of students' social skills and the relationship between the social skills and learning outcomes of the basic chemistry student course in the first semester of the Biology Education Department, Faculty of Teacher Training and Education, University of Mataram. The sample of this study was saturated consisted of 49 students. This study is descriptive quantitative research with quantitative correlational design, and data collection techniques were conducted by giving research instruments in the form of questionnaires. The results showed that the first-semester student had social skills mainly in the moderate category (59.18%). There was a positive and significant relationship between social skills and students' learning outcomes. The value of the coefficient of determination of X2 against Y (r2x2y) is 0.400. It shows that the social skill variable contributes to chemistry learning achievement by 40%, while other variables determine 60%.